Peran Muhammadiyah dalam Bidang Sosial dan Kesehatan Masyarakat Kini dan Nanti - Sukmawaty, Ice; Rahmat Sumawilaga, Rd. Andri; Ratri Wibowo, Neko (Penerbit Minhaj Pustaka, 2025)
The aim of this research is to describe the social and health movements carried out by Muhammadiyah as a leadingIslamic organization in Indonesia. This research uses a qualitative methodology with a pushtakaan approach. The research results show that Muhammadiyah's contribution to the social sciences of Indonesian society is largely divided into three areas: socialsciences, education, and modern schools. This health service sector consists of several hospitals, maternity homes, polyclinics, and similar areas of social assistance, but also orphanages, nursing homes, and other charitable assistance.